Capturing the heterogeneity of sub-national production in global trade flows. (1st December 2018) - Croft, Simon A.; West, Christopher D.; Green, Jonathan M.H.
Abstract: With increasingly complex and globalised supply chains, agricultural production and related impacts are often far removed from the point of final demand and difficult to trace. Accurately linking consumption to production is essential to understand drivers, key actors, and to facilitate actionable adaptation strategies to minimise negative impacts and guarantee food security. Here a hybridised multiregional input-output (MRIO) model, IOTA, is introduced. IOTA utilises sub-national and national level production, trade and environmental data, national scale commodity-use data, and a global economic MRIO, to link sub-national production and associated impacts to regional final consumption. In an example case-study, applying the model to Brazilian soy production and related land use for EU consumption, the relative levels of production in Brazilian states to meet EU demand differ from those of total production, and differ further still between the EU's constituent countries. Patterns can also vary considerably within a country's consumption profile depending on the sector of purchase. The linking of consumption to sub-national production and trade allows for more accurate and meaningful connections to be made between consumer behaviour and the associated impacts and risks. This enhanced understanding of consumption-driven impacts in turn informs, and allows for, more targeted and effective policy interventions to tackle the pressures and risks associated with agricultural commodity production for a global market.